Putative Nox2 inhibitors worsen homocysteine-induced impaired acetylcholine-mediated relaxation - Smith, Renee M; Rai, Sudarshan; Kruzliak, Peter; Hayes, Alan; Zulli, Anthony (NMCD. Nutrition Metabolism and Cardiovascular Diseases, 2019)
BACKGROUND AND AIM: Increased homocysteine (Hcy) is associated with coronary artery disease (CAD). Hcy increases reactive oxygen species (ROS) via NADPH oxidases (Nox), reducing acetylcholine-mediated vasorelaxation. We aimed to determine if putative Nox2 inhibitors prevent Hcy-impaired acetylcholine-mediated vasorelaxation. METHODS AND RESULTS: New Zealand White rabbit and wild-type (C57BL/6) and Nox2-/- (NOX) mice aortic rings were mounted in organ baths. Rabbit rings were incubated with either apocynin (10 μM), gp91ds-tat (GP, 1 μM) or PhoxI2 (1 μM) and mice rings GP (1 μM) only. Some rabbit rings were incubated with 3 mM Hcy, before pre-contraction, followed by dose-response relaxation to acetylcholine (ACh; 0.01μM-10μM). In rabbit rings treated with Hcy and GP, O2‾ donor pyrogallol (1 μM) or Akt activator SC79 (1 μM) was added 5 min before ACh. Mice rings were used to compare Nox2 deletion to normal acetylcholine-mediated relaxation. In rabbits, Hcy reduced acetylcholine-mediated relaxation vs. control (p < 0.0001). Treatment + Hcy reduced relaxation compared with treatment alone (p < 0.0001). Pyrogallol and SC79 reversed the response of GP + Hcy (p = 0.0001). In mice, Nox2 deletion reduced acetylcholine-mediated vasorelaxation. Rabbit tissue analysis revealed that Hcy reduced eNOS phosphorylation at Thr495 and increased eNOS phosphorylation at Ser1177; no further alteration at Thr495 was observed with GP. In contrast, GP prevented increased phosphorylation at Ser1177. CONCLUSIONS: Apocynin, GP and PhoxI2 worsens acetylcholine-mediated vascular relaxation in rabbit aorta, which is supported by results from mouse Nox2 deletion data. These inhibitors worsen Hcy-induced vascular dysfunction, suggesting that current putative Nox2 inhibitors might not be useful in treating HHcy.
Keywords: aorta; glykoproteiny; vazodilatace; Male; Mice, Knockout; Nitric Oxide Synthase Type III; fosforylace; vazodilatancia; techniky in vitro; Phosphorylation; mužské pohlaví; Enzyme Inhibitors; Acetylcholine; NADPH Oxidase 2; Glycoproteins; králíci; Vasodilator Agents; myši knockoutované; Vasodilation; Aorta; Acetophenones; Animals; homocystein; synthasa oxidu dusnatého, typ III; zvířata; In Vitro Techniques; myši inbrední C57BL; Rabbits; NADPH-oxidasa 2; acetylcholin; threonin; Mice, Inbred C57BL; Threonine; Serine; inhibitory enzymů; Homocysteine; serin; acetofenony